Krasnyi kvadrat . Krasnyi kvadrat . Red Square Box . Красный квадрат - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Opening of the Constitutional Convention - live broadcast from the Kremlin. Contributors: Liubimov, Aleksandr Mikhailovich (Anchor) Series description: Analytic talk show on the most current political issues. The program is the successor of the program "Vzgliad" ([The View] which in 1991 was renamed into "Red Square." In autumn 1993 "Red Square" was discontinued. Открытие Конституционного совещания - Прямая трансляция из Кремля. Создатели: Любимов, Александр Михайлович (Ведущий/Ведущая) Описание серии: Аналитическое ток-шоу о наиболее важных политических событиях. Программа является наследницей передачи "Взгляд," которая с 1991 года была переименована в "Красный квадрат." Осенью 1993 года "Красный квадрат" был закрыт.